The Influence of Full Day School Learning Methods on Student Motivation in Grade XI of SMA Negeri 1 Plemahan, Kediri with Emotional Intelligence as a Moderator Variable - Oky Urtya Dani* (Airlangga Development Journal, 2019)
In the teaching and learning process, motivation plays a huge role in learning achievement. Emotional Intelligence can also influence the learning achievement. The purpose of this research is to test and analyze the effect of full-day school learning methods on the learning motivation of class XI students of SMA Negeri 1 Plemahan, Kediri with emotional intelligence as a moderator variable. This research involved 160 respondents with quantitative approach methods. The data obtained will be analyzed using multiple linear analysis techniques. The result of this study indicates that there is an effect of full-day school learning methods on student motivation with a significance value of 0,000 <0.10. Furthermore, the multiple linear regression analysis with emotional intelligence as a moderator variable showed that the emotional intelligence variable succeeded in moderating the effect of full-day school learning methods on student motivation with a significance value of 0.005 <0.05.